2020
DOI: 10.1007/s11126-020-09836-0
|View full text |Cite
|
Sign up to set email alerts
|

“The COVID-19 Pandemic and its Effect on Mental Health in USA – A Review with Some Coping Strategies”

Abstract: The COVID-19 pandemic has resulted in enormous losses in terms of human lives and economy in United States. The outbreak has been continuing to heavily impact the mental health of people. Developing key strategies to prevent mental illnesses is extremely important for the well-being of people. A survey conducted during the last week of March 2020 showed that 72% of Americans felt that their lives were impacted by the outbreak, which was a 32% increase from the survey conducted only 2 weeks earlier. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 44 publications
5
87
0
8
Order By: Relevance
“…There Number of patients exposed −.45 .08 Extent of stress: Risk of transmitting to family member, and/or member of household? 2 .45 .08 Contracting disease 2 .49 .053 Finance 2 .13 .63 Not spending times with family/friends 3 .36 .17 Avoiding physical contact with others 3 .57 .02 Tension at work 3 . "Being furloughed recently has helped my stress regarding the disease but increased my stress regarding the unknown future and finances."…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There Number of patients exposed −.45 .08 Extent of stress: Risk of transmitting to family member, and/or member of household? 2 .45 .08 Contracting disease 2 .49 .053 Finance 2 .13 .63 Not spending times with family/friends 3 .36 .17 Avoiding physical contact with others 3 .57 .02 Tension at work 3 . "Being furloughed recently has helped my stress regarding the disease but increased my stress regarding the unknown future and finances."…”
Section: Resultsmentioning
confidence: 99%
“…As of November 10, 2020, global cases have reached over 50.9 million, with over 10 million cases in the United States [ 1 ]. The outbreak has resulted in a heavy psychological impact on people, especially those healthcare workers (HCWs) working at the frontline of the pandemic [ 2 ]. These unprecedented times are likely to increase severity of pre-existing mental health problems, both during the pandemic and in its aftermath [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the minority of patients with mild symptoms of COVID‐19 were still suffering from psychological symptoms and the most common psychological symptoms are phobic anxiety, paranoid ideation, and psychoticism, which indicate that psychological symptoms in patients with mild symptoms of COVID‐19 cannot be ignored. Current research (Bhattacharjee & Acharya, 2020; Li & Gang, 2020; Poudel & Subedi, 2020; Rogers et al., 2020) has found that the COVID‐19 epidemic is hazardous to patients' mental health and may result in the onset of psychiatric illness. The COVID‐19 outbreak has caused a range of psychiatric symptoms similar to that of SARS outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason is that after the patients were confirmed with COVID‐19, they were isolated for treatment and observation, and could not casually contact the outside world. As a result, many patients had difficulty adapting to the unfamiliar medical environment, were unable to obtain adequate social support from their families, feared infecting their family members, or death from the diseases (Bhattacharjee & Acharya, 2020; Liu et al., 2003). These may generate a series of psychiatric symptoms, such as phobia, generalized anxiety, social phobia, and panic disorder (Arroliga et al., 2005; Lau et al., 2005; Moreau & Zisook, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A synthesis of the limited research on COVID-19 and prior disease outbreaks determined that pandemics/outbreaks and the associated public health sequelae (e.g., quarantine, social isolation) are associated with symptoms of depression and anxiety, which may elevate as social distance guidelines remain in place for longer periods and persist after the pandemic is under control ( Brooks et al, 2020 ; Chew et al, 2020 ; Liu et al, 2020 ; Torales et al, 2020 ). To date, evidence suggests that the COVID-19 pandemic is associated with an increase in negative emotionality and decrease in positive emotionality ( Bhattacharjee & Acharya, 2020 ; Li et al, 2020 ). Only 2 to 4 months into the pandemic, mental health services saw dramatic increases in behavioral health service utilization (e.g., SAMHSA hotline; Cuningham, 2020 ) as more than half of Americans reported worsening mental health ( KFF Health Tracking Poll, July, 2020 ).…”
Section: Introductionmentioning
confidence: 99%